2001
DOI: 10.1038/sj.ijo.0801638
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of obesity distribution and peripheral arterial occlusive disease in elderly men

Abstract: OBJECTIVE:To examine the relationships between total body fatness and abdominal fat distribution with peripheral arterial disease. DESIGN: Cross-sectional. SUBJECTS: Population-based sample of 708 men aged 55±74. MEASUREMENTS: Body mass index (BMI) to estimate total body fatness and waist-to-hip ratio for abdominal fat distribution; peripheral arterial disease de®ned by ankleabrachial index`0.9; cardiovascular risk factors. RESULTS: Peripheral arterial disease was observed in 13.4% of subjects. BMI did not cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 18 publications
3
34
0
Order By: Relevance
“…A previous study reported a relationship between abdominal adiposity and PAD 23,24) . WC may be associ- Receiver operating characteristic curves of PAD from the selected models (Table 3) for 900 male ( Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A previous study reported a relationship between abdominal adiposity and PAD 23,24) . WC may be associ- Receiver operating characteristic curves of PAD from the selected models (Table 3) for 900 male ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Age and dyslipidemia were associated with most of the previously reported conventional risk factors for PAD-related factors 5,[8][9][10] ; however, few studies have reported WC as an independent risk factor for PAD 23,24) . A previous study reported a relationship between abdominal adiposity and PAD 23,24) .…”
Section: Discussionmentioning
confidence: 93%
“…26,27 The discrepancy may be related to the higher prevalence of PAD in elderly males and in smokers; elderly males show a weaker relationship between obesity and CVD, and smokers tend to have lower BMI than non-smokers. 28 A recent prospective cohort study revealed a positive relationship between waist-to-hip ratio, not BMI, and PAD prevalence. 29 Mechanisms by which obesity may cause PAD (if any) could be different to those for CHD, as they do have different risk profiles (eg, cigarette smoking is more strongly associated with the development of PAD than CHD).…”
Section: Peripheral Arterial Disease (Pad)mentioning
confidence: 98%
“…Obesity is usually observed in PAD patients [7] . Nevertheless, although the effects of obesity and PAD decreasing exercise tolerance and compromising vascular function have been well defined [4,8] , the effects of their associations on these aspects are not well documented.…”
mentioning
confidence: 99%